The Effectiveness of Using an E-Book in ELT: Worldwide Cases - Nurul Fitriyah Almunawaroh (Siliwangi University, 2020)
Using technology in English language teaching has been demands in Covid-19 pandemic situation. Students all over the world have studied from home, so have the teachers. Therefore, using technology is necessary as a medium in teaching the English language. It is necessary to use a technology that has interactive functions to ensure the quality of teaching and learning, as well as to keep students’ motivation high. This study is a library study which aimed to analyze the effectiveness of using E-book in ELT from previous related studies worldwide from 2015-2019. Further implications on the effectiveness of using e-book and suggestions to the future studies were discussed.